Expression of apoptosis inhibitor of macrophages in tissue macrophages, leukocytes and vascular endothelial cells of dogs. (June 2019) - Uchida, M.; Uchida, K.; Maeda, S.; Yonezawa, T.
Graphical abstract: Highlights: Canine AIM was expressed in tissue macrophages in the spleen, liver, lung, lymph nodes and bone marrow but not in the cerebrum. Canine AIM was expressed in B lymphocytes in the lymph nodes and peripheral blood. Monocytes and microvascular endothelial cells also expressed AIM. There were AIM positive cells in proximal tubules in the kidney and pyramidal cells in the cerebrum. Abstract: Apoptosis inhibitor of macrophages (AIM) is a protein which plays important roles in controlling the immune response and inflammation in human and mice. In dogs, AIM is reported to be expressed in cancerated macrophages and regulate the survival of these tumor cells. In this study, to elucidate the physiological expression pattern of AIM in dogs, systemic expression and distribution of AIM of dogs were investigated. Mature healthy Beagles were used. Various tissues, peripheral blood cells, and bone marrow cells of normal dogs were collected for in situ hybridization, real-time RT-PCR, and immunohistochemistry. AIM mRNA and protein were expressed in tissue macrophages of the spleen, liver, lungs, and lymph nodes, but not in the microglia of the cerebrum. Proximal tubules in the kidney also expressed AIM protein. Monocytes and B lymphocytes in circulating blood and a part of microvasculature endothelial cells showed AIM expression at both the mRNA and protein levels. In the bone marrow, early-stage monocyte progenitor-like cells expressed AIM mRNA and protein. These results clarified that AIM is expressed in more cell types than previously reported in human and mice. These data spread the possibility of AIM physiological functions and implies the relationship of AIM to the maturation of macrophage-strain cells in dogs and other species.